Characterization of DNA polymerase and RNA associated with A-type particles from murine myeloma cells. - Robertson, D L (1975)
The RNA-dependent DNA polymerase present in intracisternal A-type particles from mouse myeloma tumor cells has been studied. This polymerase can use either endogenous A particle RNA or an exogenous synthetic polynucleotide [poly (rA)] as a template. The DNA reaction product is small (4S-10S) and over 90% of it hybridizes to A particle RNA, whereas up to 50% of it hybridizes to murine sarcoma-leukemia virus RNAs. The RNA isolated from purified A particles is generally of low molecular weight (5S-15S) but contains small amount of 70S and 35S components. These results suggest that A-type particles may be related to C-type oncornaviruses.